ENVIRONMENTAL FACTORS IN MONITORING HOSPITAL CARE EFFECTIVENESS INDICATORS - Silvestre, Alexandra Lunardon; Wolff, Lillian Daisy Gonçalves; Figueiredo, Karla Crozeta; Gelbcke, Francine Lima; Alves, Marília; Seiffert, Leila Soares (Cogitare Enfermagem, 2024)
Objective: To identify environmental factors that favor monitoring care effectiveness indicators in the dimensions of safety and patient-centered care in hospitals. Method:Qualitative research with multiple cases study, carried out in three hospitals in south Brazil, involving 58 participants. Data was collected between June 2020 and December 2021 through questionnaires, interviews, focus groups, and institutional documents subjected to categorical content analysis. Results: The following categories were identified: internal and external environmental factors; and subcategories: convergent and non-convergent, namely: internal convergent - strategic planning and management support for quality management, information systems, and institutional strategies, methods and procedures; internal non-convergent: public teaching hospital; and external convergent - public policies and epidemiological factors; and non-convergent - accrediting agency and hospital network. Conclusion: Factors favoring the monitoring of effectiveness indicators were found in the dimensions considered, which elucidate good quality management practices that are useful and relevant to Brazilian hospitals.